Urban Climate Mitigation through NDVI and Albedo Monitoring: A Case Study in Kendari, Indonesia - Muna, Siti Umamah Naili; Munawir, Abdillah (ASTONJADRO, 2026)
The objective of this research is to apply spatial analysis of the Normalized Difference Vegetation Index (NDVI), albedo, and air temperature in Kendari City to identify the types of land use change resulting from changes in the vegetation of the Nipa-Nipa-forest area, the air temperature trend over the last 10 years, and to map areas with high mitigation needs. The method used is the spatial analysis of Landsat satellite imagery through supervised classification supported by ground check points to test the accuracy of 10 land use types. Air temperature analysis, and NDVI and albedo analysis are extracted from surface reflectance data to evaluate vegetation conditions and surface energy changes. The results show that air temperature variability is influenced by the duration of sun exposure and altitude. The diurnal pattern indicates that the temperature peaks at two in the afternoon and decreases again toward evening. At an altitude of 21.7 meters, the temperature is relatively lower during the day and higher at night compared to other layers. The Nipa-Nipa Grand Forest still dominates with the highest NDVI values, but has decreased in some zones due to forest fragmentation. Meanwhile, built-up areas and open land have experienced a significant increase with low NDVI values and high albedo, which indicates a reduction in vegetation quality and an increased potential for the urban heat island effect. Albedo values in vegetated areas, such as forests and mangroves, decreased between 2017 and 2022, indicating ecosystem degradation. The classification accuracy test yielded an overall accuracy of 94% and a Kappa value of 0.92, which shows a very high level of reliability and consistency with international research standards. The contribution of this research is to provide a spatial data-based scientific foundation regarding ecological dynamics in tropical urban areas, especially the role of the Nipa-Nipa Grand Forest as a climate buffer. These findings can support sustainable spatial planning, conservation strategies, and climate change mitigation efforts in Kendari City and similar regions.